Effectiveness of a phone-based nurse monitoring assessment and intervention for chemotherapy-related toxicity: A randomized multicenter trial - Antonuzzo, Andrea; Ripamonti, Carla Ida; Roila, Fausto; Sbrana, Andrea; Galli, Luca; Miccinesi, Guido; Sammarco, Enrico; Berruti, Alfredo; Coletta, Deborah; Velutti, Laura; Fabi, Alessandra; Corsi, Domenico Cristiano; et al. (Frontiers in Oncology, 2022)
PURPOSE: Anticancer treatment-related toxicities can impact morbidity and mortality, hamper the administration of treatment, worsen the quality of life and increase the burden on the healthcare system. Therefore, their prompt identification is crucial. NICSO (Italian Network for Supportive Care in Cancer) conducted a nationwide randomized trial to evaluate the role of a planned, weekly phone-based nurse monitoring intervention to prevent and treat chemotherapy, targeted therapy- and immunotherapy-related toxicities. Here, we report the results from the chemotherapy arm. METHODS: This was a nationwide, randomized, open-label trial conducted among 29 Italian centers (NCT04726020) involving adult patients with breast, colon, or lung cancer and a life expectancy ≥6 months receiving adjuvant chemotherapy. Patients received either a weekly nurse monitoring phone call and an educational leaflet reporting practical advice about prevention and treatment of toxicities (experimental group) or the educational leaflet only (control group). RESULTS: The addition of a nurse monitoring intervention may help reduce time spent with severe toxicities (grade ≥3), particularly those less frequently reported in clinical practice, such as fatigue. When considering grade 1–2 AEs, times with mild/moderate diarrhea, mucositis, fatigue and pain were shorter in the experimental arm. Time spent without AEs was significantly longer in the experimental arms for all the toxicities. The requirement for special medical attention was comparable between groups. CONCLUSION: This study suggests the need for implementing a better system of toxicity assessment and management for patients treated with adjuvnt chemotherapy to promote effective preventive and/or therapeutic intervention against these events.